2012
DOI: 10.1002/jbmr.1725
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the dynein-dynactin complex unveils motor-specific functions in osteoclast formation and bone resorption

Abstract: Osteoclastic bone resorption requires strict interplay between acidified carrier vesicles, motor proteins, and the underlying cytoskeleton in order to sustain the specialized structural and functional polarization of the ruffled border. Cytoplasmic dynein, a large processive mechanochemical motor comprising heavy, intermediate, and light chains coupled to the dynactin cofactor complex, powers unilateral motility of diverse cargos to microtubule minus-ends. We have recently shown that regulators of the dynein m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Consistent with this possibility, we have previously found that LIS1 regulates the survival of osteoclast precursors by modulating JNK activation (38). Similarly, disturbance of dynein function impairs osteoclast differentiation and function (80). Loss of Plekhm1 caused dramatic morphological changes in osteoclasts but did not affect the number of mature osteoclasts cultured on plastic (Figure 4 and Supplemental Figure 3).…”
Section: Discussionsupporting
confidence: 70%
“…Consistent with this possibility, we have previously found that LIS1 regulates the survival of osteoclast precursors by modulating JNK activation (38). Similarly, disturbance of dynein function impairs osteoclast differentiation and function (80). Loss of Plekhm1 caused dramatic morphological changes in osteoclasts but did not affect the number of mature osteoclasts cultured on plastic (Figure 4 and Supplemental Figure 3).…”
Section: Discussionsupporting
confidence: 70%
“…MTs play a central role in processes essential for OC activity and bone resorption: polarization of the cells (66), vesicular traffic (67)(68)(69)(70)(71)(72), motility (68), and podosome belt formation (21,23,24,70,(73)(74)(75). Formation of the podosome belt has been the focus of this study because if other cell types use podosomes/invadosomes to migrate, adhere, and degrade the extracellular matrix (7), OCs are the only cells where podosomes follow a precise patterning such that clusters form rings that fuse and expand to form a characteristic peripheral belt (6,7,12), establishing the sealing zone when OCs are plated on bone or dentin (11).…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule organization, intracellular vesicular trafficking, and the activity of dynein motor are critical for the activation and function of osteoclasts (46)(47)(48). LIS1 was recently identified as a microtubule regulator that interacts with both Plekhm1, a component of late endosomal trafficking, and the dynein-dynactin motor complex in osteoclasts (47).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of LIS1 dramatically inhibited the formation and bone resorption function of osteoclasts by interfering with dynein function and microtubule organization (47). Exogenous expression of dynamitin, a component of the dynactin complex, disrupted the dynein-dynactin complex, leading to retardation of osteoclast formation (48). Therefore, the role of LC8 in osteoclast differentiation as an essential component of the dynein motor complex may be worthy to be studied.…”
Section: Discussionmentioning
confidence: 99%